KEDUDUKAN PENYELESAIAN KASUS HUKUM PERDAGANGAN INTERNASIONAL TENTANG IMPOR UDANG: Vol 06 Nomer 02 September 2019 - H. Noho, Muhammad Dzikirullah (Irtifaq, 2019)
The case of shrimp imports carried out by India, Malaysia, Pakistan and Thailand was banned by America because the way of shrimp fishing endangers the environment because it kills sea turtles. Starting from the problem, the issues to be discussed, namely the resolution of the shrimp import case carried out by the United States, are in accordance with the principles and rules mentioned in the general agreement tariff on trade (GATT). Based on the results of the discussion, it was found that the import ban regulation called public law 101-102, Sextion 609 was codified in 16 United States Code (USC by America refers to CITES (Convention on International Trade in Endangered Species of Wild Fauna and Flora). for countries complaining that the import prohibition cannot be included in the exception cases contained in article XX GATT and accuses the US of violating GATT article XI on "quantitative restrictions. DSB Appeal Decision states that US actions are declared" temporarily correct "because even though included in the exclusion of article XX GATT, but does not meet procedural requirements, so that proposals for improving the rules are stipulated so that they can be justified, so that the rules can be enforced by the US and no longer considered as acts of arbitrary discrimination. Keywords: Settlement, International Trade, Shrimp Imports